Kadar Asam Klorogenat (CGA) Dalam Biji Kopi Arabika (Coffea Arabica) Asal Wamena, Papua - Septiani Mangiwa; Alowisya Futwembun; Puteri M. Awak (Universitas Pendidikan Mandalika Mataram, 2015)
Chlorogenic acid (CGA) is one of chemical compound in coffee and class of polyphenolic compounds that have activity as antioxidant. This study aims to determine the CGA contain in Arabica coffee beans from Wamena regency of Jayawijaya, Papua. Coffee beans were roasted by three roasting temperature i.e. 75, 150 and 2250 C while unroasted one was used as controls. Extraction was performed by soxhletation using metanol as a solvent for 5 hours. Separation and CGAcontent were determined using HPLC uses C-18 column, 150 mm length, 4,6 mm in diameter, with metanol-fosfat buffer 10 mM pH 2,6(30:70) as eluent, flow rate of 1 mL/minutes, injection volume of 20 µL and measured by spectrophotometer UV-Vis in 329 nm. The result of the study shows the CGAcontent in treated beans with temperature roasting of 75, 150 and 2250C respectively were 6,93 ; 9,33 and 7,12 % while the unroasted one was 7,73 %. The lowest CGA content was found in coffee beans roasted in 750C while the highest in 1500 C.